African Swine Fever in Indonesia: Insights from Southeast Asia’s Policy Response through The One Health Approach - Salindri, Niken; Sulistiadi, Wachyu (Journal of Indonesian Health Policy and Administration, 2025)
African Swine Fever (ASF) seriously threatens pig production systems, food security, and rural livelihoods across Southeast Asia. This study employs an analysis of secondary national data from Indonesia using a quantitative descriptive analysis approach, complemented by regional policy responses to ASF from 2019 to 2024. To contextualize regional findings, this study also integrates official statistics from Statistics Indonesia (BPS) covering provincial pork production trends (2021–2023), the number of ASF-affected pigs per province (2020–2024), and per capita pork consumption by district. Quantitative data show that ASF outbreaks have been disproportionately concentrated in specific provinces such as East Nusa Tenggara and North Sumatra, significantly impacting national pork production and local consumption trends. The average provincial ASF case numbers trend reveals a sharp decline after 2021, with notable fluctuations across subsequent years. These findings highlight the urgent need for harmonized surveillance, stronger biosecurity practices, and the development of context-specific policies that address ASF's epidemiological and socio-economic dimensions. The study underscores the importance of integrating scientific research, government data, and regional coordination to improve Southeast Asian ASF preparedness and response strategies.